Statistical process control applied to airblast sprayer on a coffee crop - Ribeiro da Silva, João Eduardo; Arantes Rodrigues da Cunha, João Paulo; Siqueira Schroden Nomelini, Quintiliano (Coffee Science - ISSN 1984-3909, 2016)
The objective of this work was to study the quality and variability, from a statistical process control point of view, of the deposition on coffee crop leaves and the loss to the soil promoted by pulverization with an air-blast sprayer using different application volumes and droplet sizes. The experiment was carried out in Arabica coffee crop using the 2x2 factorial design and eight replicates, with the factors being the droplet sizes generated by two types of nozzles (hollow cone - ATR - which produced fine droplets, and hollow cone with air induction - TVI - which produced extremely large drops) and spray application volumes (200 and 500 L ha-1). Brilliant Blue tracer was used to quantify by spectrophotometry the spray deposits on the leaves of the top and bottom halves of the plant and on the ground targets. The statistical quality of sprays was evaluated using statistical process control. Control charts show that there is no detectable patterns of non-randomness within treatments, ensuring the good quality of the pulverizations in the coffee crop. The spraying using the volume of 500 L ha-1 provides flexibility in the choice of hydraulic nozzle, keeping quality and low variability of deposition in the coffee leaves.